Time in hemodialysis modulates the levels of genetic damage in hemodialysis patients. (17th January 2014) - Rodríguez‐Ribera, Lara; Stoyanova, Elitsa; Corredor, Zuray; Coll, Elisabet; Silva, Irene; Diaz, Juan Manuel; Ballarin, José; Marcos, Ricard; Pastor, Susana
<x xml:space="preserve">Abstract</x> It is assumed that hemodialysis treatment can diminish the levels of genetic damage in circulating lymphocytes by cleaning the blood of uremic toxins that cause oxidative stress. However, the hemodialysis process by itself may also induce genomic damage by producing reactive oxygen species (ROS). We conducted a follow‐up study in a group of 70 hemodialysis patients followed for a mean time of 15 months. We investigated the effect of exposure time in hemodialysis on the levels of genetic damage in peripheral blood lymphocytes using the micronucleus assay. In addition, genetic damage after in vitro irradiation with 0.5 Gy was also analyzed to evaluate changes in radiosensitivity. Our results showed that, at the end of the study, there was a decrease in both the basal levels of genetic damage (9.9 ± 1.0 vs. 7.6 ± 0.7) and radiosensitivity values (38.5 ± 3.0 vs. 27.6 ± 2.4). We conclude that hemodialysis procedures may act as an ameliorating factor reducing the genetic damage present in chronic kidney disease patients. Environ. Mol. Mutagen. 55:363–368, 2014. © 2014 Wiley Periodicals, Inc.